INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE, AND SOCIAL MEDIA ON THE CONSUMPTIVE BEHAVIOR OF GENERATION Z STUDENTS IN THE FACULTY OF ECONOMICS AND BUSINESS FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Tarisa Zikria Maghfira; Yulius Dharma; Munardi; Fuadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of financial literacy, lifestyle, and social media on the consumptive behavior of Generation Z students in the Faculty of Economics and Business at Malikussaleh University from an Islamic economic perspective. Generation Z is known for its high tendency toward consumptive behavior due to the intensive use of social media, modern lifestyles, and low financial literacy. This research uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression to test both partial and simultaneous effects of the independent variables on consumptive behavior. The results show that partially, financial literacy has a negative and significant effect on consumptive behavior, indicating that higher financial literacy reduces students' consumptive tendencies. Meanwhile, lifestyle and social media usage have positive and significant effects, meaning the higher the lifestyle orientation and social media intensity, the greater the level of consumptive behavior. Simultaneously, all three variables significantly affect consumptive behavior. From the perspective of Islamic economics, excessive consumption (israf) is prohibited, as it contradicts the principles of moderation and balance in consumption. This study recommends strengthening Islamic financial literacy education from an early age to reduce consumptive behavior and build students' awareness to adopt rational and responsible consumption practices in accordance with Islamic principles as outlined in the Qur'an.